2020
DOI: 10.1002/fam.2915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of upholstery materials on the burning behavior of real‐scale residential upholstered furniture mock‐ups

Abstract: Fire spread and growth on real-scale four cushion mock-ups of residential upholstered furniture (RUF) were investigated with the goal of identifying whether changes in five classes of materials (barrier, flexible polyurethane foam, polyester fiber wrap, upholstery fabric, and sewing thread), referred to as factors, resulted in statistically significant changes in burning behavior. A fractional factorial experimental design plus practical considerations yielded a test matrix with 20 material combinations. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Pitts et al examined the changes in fire spread and fire growth on real-scale furniture upholstered with different materials, including barrier, fabric, sewing thread, wrap, and foam [ 178 ]. The ability to ignite the furniture was dependent on the material, with the barrier, fabric, and foam having the most statistically significant effect, and thread and wrap having the least significant effect on burning characteristics.…”
Section: Fire Researchmentioning
confidence: 99%
“…Pitts et al examined the changes in fire spread and fire growth on real-scale furniture upholstered with different materials, including barrier, fabric, sewing thread, wrap, and foam [ 178 ]. The ability to ignite the furniture was dependent on the material, with the barrier, fabric, and foam having the most statistically significant effect, and thread and wrap having the least significant effect on burning characteristics.…”
Section: Fire Researchmentioning
confidence: 99%
“…Pitts and co‐workers conducted tests on real‐scale four‐cushion mockups of residential furniture to identify the extent to which changes in materials led to significant changes in burning behavior 15 . The cushion variables were the upholstery fabric (thermoplastic or cotton), the type of FPUF, the presence of a polyester fiber wrap around the foam, the presence of one of two fire barrier layers under the fabric, and the type of sewing thread.…”
Section: Controlling the Hazards From Upholstered Furniture Firesmentioning
confidence: 99%
“…Of particular note in the context of furniture-scale calorimetry is the recent work of the National Institute of Standards and Technology (NIST) in the US. This group has produced a series of recent publications that outline the fire performance of upholstered furniture and describe techniques to mitigate the burning of upholstered chairs [10,[19][20][21][22][23]. These studies have identified various aspects that influence the growth rate of upholstered furniture fires (e.g., generation of a pool fire beneath the item) and present a range of solutions to improve furniture safety, such as passive fabric barriers within the make-up of the item which can greatly reduce the peak HRR.…”
Section: Introductionmentioning
confidence: 99%